Social Expenditure in Taiwan (China) - Chow, Peter C.Y. (Washington, DC: World Bank, 2013)
Social expenditures in Taiwan (China) accelerated during recent decades, in accordance with economic development, social transformation, and democratization. Among the various categories of expenditure, education spending received the highest priority, and continues to do so up to this day. Furthermore, the government was able to match its human resource development targets, with the actual needs of the economy, while promoting competition among individuals for educational advancement. Spending on another priority area - social security - has risen gradually with social security programs, initially covering only a small targeted segment of the population, and then expanding to cover a wider cross-section of the society. Meanwhile, a comprehensive National Health Insurance (NHI) was introduced only a few years ago (in 1995). The hallmark of Taiwan (China's) approach to social policy has thus been gradualism. This aspect has helped it avoid fiscal crises, due to unsustainable social spending. However, democratization in recent years will likely accelerate such spending.